Development potential for Sungai Langat in Selangor for water transportation operation - Nur Hidayah Abdul Ghani, 1985-; Ab. Saman Abd. Kader; Fakulti Kejuruteraan Mekanikal (2009)
Project Paper (Sarjana Muda (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2009